INTEGRASI ILMU KEISLAMAN DAN FILSAFAT: PERSPEKTIF FILSAFAT ILMU - Wardani Wardani (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2019)
This article intends to examine the integration between Islamic studies and philosophy from the philosophy of science perspective. The focus of this study primarily focuses on Islamic studies in Islamic university in Indonesia, regarding the real conditions of its science seen from the perspective of philosophical learning. The second focus is the offer of the philosophy of science approach in developing Islamic studies. The article concludes that Islamic studies at the university are “poor of philosophy